NW-dipping versus SE-dipping causative faults of the 1783 M7.1 Southern Calabria (Italy) earthquake: The contribution from the analysis of the coseismic hydrological changes - Cucci, Luigi (Frontiers in Earth Science, 2022)
The 1783 M7.1 Southern Calabria (Italy) earthquake originated a remarkable dataset of 78 observations of hydrological changes (variations of flow in springs and streams, liquefaction, changes in water temperature) that occurred in 53 different localities. To provide further constraints on the mechanism and the geometry of the still debated causative fault of the event, I compared the distribution of the hydrological changes with the coseismic strain produced by eight seismogenic sources proposed for the earthquake. The most important outcomes of the study can be summarized as follows: a) the group of potential sources that display the best agreement between expected deformation and hydrological signature consists of NW-verging systems of three to four surface-rupturing almost pure normal fault segments (Cittanova system), capable of generating earthquakes of magnitude M6.9-M7.1; b) the distribution of the observed coseismic hydrological anomalies does not support the role of the SE_dipping faults as potential sources of the 1783 earthquake; c) the pattern of deformation associated with the best fit source strengthens the hypothesis that the 20 km-long surface ruptures testified soon after the 1783 event reflect primary faulting; d) a minimum magnitude M6.9-7.0 is required to obtain the pattern and the extent of distribution of the coseismic hydrological changes observed in the field; e) the location of the hydrological variations that were observed only along the western side of southern Calabria can be evidence that the Cittanova system of faults acts as a hydrological barrier that hampers the groundwater circulation toward the East.